Peranan Audit Operasional Dalam Menunjang Efektivitas Penjualan Pada PT. Intan Pariwara Maumere - Bernadeta Yosefin; Yosefina Andia Dekrita; Paulus Libu Lamawitak (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the role of operational audits in supporting sales effectiveness at PT. Intan Pariwara Maumere. The research method used is descriptive qualitative. The data sources used in this research are primary data and secondary data. Data collection techniques used in this research were observation, interviews and documentation. Data analysis techniques in this research include data reduction, data presentation, and verification. The research results show that the audit carried out at PT. Intan Pariwara Maumere is in accordance with the operational audit stage which consists of the preliminary audit stage, in-depth audit stage and audit reporting stage. The strategy carried out by PT. Intan Pariwara Maumere to achieve sales targets, namely through promotions to agencies, distributing brochures and placing pamphlets as promotional media. Based on the results of data analysis, it can be concluded that sales at PT. Intan Pariwara Maumere is not yet effective, because it has not reached the sales target set by the company, namely 80% per year. The results obtained from the role of operational audit at PT. Intan Pariwara Maumere is in the ineffective category, which can be seen from sales targets and realization that have not reached the targets set by the company, and operational audits are not carried out regularly